2016
DOI: 10.3945/ajcn.116.130633
|View full text |Cite
|
Sign up to set email alerts
|

Growth of infants consuming whey-predominant term infant formulas with a protein content of 1.8 g/100 kcal: a multicenter pooled analysis of individual participant data

Abstract: Whey-predominant infant formula with a lower protein content that more closely resembles that of breast milk supports healthy growth comparable to the WHO growth standards and close to breastfed infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 32 publications
7
26
0
2
Order By: Relevance
“…BMIAZ did not differ from 0 at any time point, except at 12 months, when it was significantly >0. HCAZ was significantly >0 at all time points; this particular finding is consistent with recent observations [18,22], which showed that WHO head circumference data are consistently lower than measurements from large studies of economically advantaged children. Collectively, these findings suggest that further considerations are needed in regard to using a single international head circumference standard.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…BMIAZ did not differ from 0 at any time point, except at 12 months, when it was significantly >0. HCAZ was significantly >0 at all time points; this particular finding is consistent with recent observations [18,22], which showed that WHO head circumference data are consistently lower than measurements from large studies of economically advantaged children. Collectively, these findings suggest that further considerations are needed in regard to using a single international head circumference standard.…”
Section: Resultssupporting
confidence: 91%
“…For growth from birth to 12 months of age, the mean change (SD) in WAZ was 0.49 (1.2); the proportion of infants in “slow”, “gradual”, and “rapid” categories was 22%, 30%, and 48%, respectively. In a recent large-scale pooled analysis of 11 randomized controlled trials [18], the proportion of infants with a WAZ change from birth to four months of age in “slow”, “gradual”, and “rapid” categories, was 27%, 52%, and 21% among infants fed lower protein formulas without active ingredients (1.8 g protein/100 kcal); was 22%, 52%, and 26% among infants fed lower protein formulas with active ingredients (1.8 g protein/100 kcal with prebiotics, probiotics, or both); and was 42%, 49%, and 9% among breastfed infants (Figure 3), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations